Implementasi Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Katolik di Sekolah Dasar Katolik Kota Malang - Derung, Teresia Noiman; Resi, Hironimus; PiusX, Intansakti; Koerniantono, Marioes Eduardoes Kakok; Mandonza, Maria (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2026)
Study results from the Program for International Student Assessment (PISA) show that 70% of 15 year old students are below minimum competency in understanding simple reading or applying basic mathematical concepts. Based on these results, the Indonesian Government, in this case the Minister of Education, offers an independent curriculum to formal education institutions. Catholic elementary schools in Malang City have implemented it, including in Catholic religious education lessons starting in 2022-2023. The aim of this research is to describe the implementation of Catholic religious learning based on the independent curriculum, especially in terms of flexible curriculum indicators, project-based learning, active learning, and teacher competency in implementing the independent curriculum. The method used is descriptive qualitative with Colaizzi model analysis, through several steps, namely: verbatim, coding, data extract, theme formulation, description. The results obtained are that the independent curriculum has been implemented, with several indicators, namely a flexible curriculum has been implemented, but there are school principals who do not understand the implementation of the independent curriculum. Project-based learning has been implemented well, but the obstacle is time constraints. Learning has been actively carried out but teachers are less creative in involving students. Catholic religious education teachers have competence in the pedagogical, professional, personal, social and technological fields but find it difficult to provide good examples or role models as competent teachers. In conclusion, the independent Catholic religious learning curriculum has been implemented but is not yet optimal.